Records of growth and development data in the child health handbook - Simone Mourão Abud; Maria Aparecida Munhoz Gaíva
OBJECTIVE: The aim was to analyse the input of growth and development data in the Child Health Handbook. METHOD: This is a cross-sectional study conducted in Cuiabá, Brazil, on August 13, 2011, with the application of a questionnaire and direct observation of 950 handbooks. We included children under one year of age who resided in Cuiabá, accompanied by their mothers or guardians who were in possession of the handbook. Data were analyzed by calculating the prevalence ratio (PR) and Chi-Square test, with a significance level set at 5%. The project was approved by the Ethics Committee under Opinion No. 882/2010. RESULTS: Of the analyzed handbooks, 95.4% of the development data and 79.6% of the data in the growth charts were incomplete or missing. CONCLUSION: The low rate of growth and development data input in the handbooks reveals the need to create awareness among the population, health care professionals and managers on the importance of handbooks, and the need to invest in training and the empowerment of professionals in relation to its proper use.